2022
DOI: 10.1021/acssuschemeng.2c04847
|View full text |Cite
|
Sign up to set email alerts
|

Potential Dependence of Ammonia Selectivity of Electrochemical Nitrate Reduction on Copper Oxide

Abstract: Nitrate electrochemical reduction (eNO 3 RR) has been considered as an alternative strategy for decentralized ammonia production, while there are two critical issues regarding high overpotential and poor selectivity because of nitrite production at low overpotentials. Therefore, it is significant to understand the reaction mechanism of ammonia and nitrite selectivity. In addition, it was found that hydrogen evolution reaction (HER) can become notable and drastically affects the Faradaic efficiency. In this wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…carried a throughout thermodynamic and kinetic study on the factors, including facets, applied potentials, and exposed surfaces, to reveal the e‐NO 3 RR reaction mechanisms of perfect and defective Cu 2 O surface. [ 134 ] The (110) and (111) facets of defective Cu 2 O exhibited better catalytic performance than pure Cu facets, consistent with the results from the hybrid Cu/Cu 2 O nanowire arrays. Differently, by dividing the 8‐electrons direct nitrate‐to‐ammonia conversion to [2+6] staged pathway, Jiang and co‐workers found that Cu° could has a high ammonia FE under ultra‐low staged potentials ( Figure a,d), which was more superior to Cu/Cu 2 O.…”
Section: Catalysts For E‐no3rrsupporting
confidence: 80%
“…carried a throughout thermodynamic and kinetic study on the factors, including facets, applied potentials, and exposed surfaces, to reveal the e‐NO 3 RR reaction mechanisms of perfect and defective Cu 2 O surface. [ 134 ] The (110) and (111) facets of defective Cu 2 O exhibited better catalytic performance than pure Cu facets, consistent with the results from the hybrid Cu/Cu 2 O nanowire arrays. Differently, by dividing the 8‐electrons direct nitrate‐to‐ammonia conversion to [2+6] staged pathway, Jiang and co‐workers found that Cu° could has a high ammonia FE under ultra‐low staged potentials ( Figure a,d), which was more superior to Cu/Cu 2 O.…”
Section: Catalysts For E‐no3rrsupporting
confidence: 80%
“…To address this, Xiao et al. developed the constant potential simulation method and the microkinetic model combined with DFT calculations, and successfully interpreted the complex U -dependent selectivity of the electrochemical nitrogen oxides reduction reactions. Due to the U -independence, *NN adsorption on Fe 2 /MX 2 systems could be regarded as a thermochemical behavior without obvious proton and electron transfer, and consequently the competition between HER and NRR at varying U can be interpreted by the *NN and *H coverages, which are determined by the Δ G values under different U . Thus, it is reasonable to explore the U -dependent selectivity of Fe 2 /MX 2 systems using the CHE model.…”
Section: Resultsmentioning
confidence: 99%
“…In short summary, the ammonia selectivity at low overpotentials is still low. It can be attributed to the diverse adsorption structure of NO 2 /HNO 2 , [15b] while all weak adsorbed NO 2 /HNO 2 species prefer to desorb, instead of being reduced to ammonia. A high ammonia selectivity at large overpotential is benefited from the small charge transfer coefficient for the chemical desorption of HNO 2 production.…”
Section: Reverse Artificial Nitrogen Cyclementioning
confidence: 99%